Optical based touch interface : algorithm and optimization - Kai, Liu (2014)
Recent growth of sensing technologies and expansion of microelectrics has greatly impacted the research and development of human-computer interface (HCI) technologies. With in the field of HCI, studies on touch interface come to the fore and have been widely applied to commercial applications ranging from small-scale gadgets such as watches and phones, to large-scale devices such as televisions and white boards. However, with the existing technology, the cost for the setup could get significantly increased if the area of interaction increases.